2019
DOI: 10.1016/j.cels.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Aging of Isogenic Yeast Cells Revealed through Single-Cell Phenotypic Dynamics

Abstract: Highlights d Single-cell phenotypic analysis reveals detailed replicative aging dynamics d Isogenic cells differentiate early in life toward two distinct aging paths d A stochastic state-transition model captures the landscape of aging dynamics d Genetic and environmental factors modulate aging trajectories and kinetics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 37 publications
(43 reference statements)
3
49
0
Order By: Relevance
“…A recent work proposed a morphological landscape of yeast aging on which the mother cells took two distinguishable aging paths: in the first path the mother cells produced enlarged and elongated daughter cells, and in the second path the mother cells produced small and round daughter cells (Jin et al 2019). The mother cells went through the first path had longer RLSs than the mother cells underwent the second path.…”
Section: Pipl On Dimensions Of Rls Versus Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…A recent work proposed a morphological landscape of yeast aging on which the mother cells took two distinguishable aging paths: in the first path the mother cells produced enlarged and elongated daughter cells, and in the second path the mother cells produced small and round daughter cells (Jin et al 2019). The mother cells went through the first path had longer RLSs than the mother cells underwent the second path.…”
Section: Pipl On Dimensions Of Rls Versus Morphologymentioning
confidence: 99%
“…The mother cells went through the first path had longer RLSs than the mother cells underwent the second path. Two morphologies were used in this landscape to infer the aging paths including the daughterto-mother size ratios for daughter cell size and the axis ratios of the daughter cells for daughter cell roundness, both at the late stages of cell growths (Jin et al 2019;Li et al 2020). Here, we combined the RLSs and took advantage of the Saccharomyces Cerevisiae Morphological Database (SCMD2) which recorded 501 morphologies of different yeast single-gene deletion mutants (Saito et al 2004;Ohya et al 2005).…”
Section: Pipl On Dimensions Of Rls Versus Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…The methodological advances achieved during the last decade allowed the study of phenotype heterogeneity in clonal cells. Particularly, the use of microorganism models has challenged the classical view of the phenotype determinacy based on the genotype and environmental context [1][2][3][4][5] .…”
mentioning
confidence: 99%
“…Using single-cell imaging technologies, we found that isogenic WT cells exhibit two different types of phenotypic changes during aging (6,7). About half of aging cells continuously produced daughters with a characteristic elongated morphology during later stages of lifespan.…”
mentioning
confidence: 99%